Galectin-9 Mediates the Therapeutic Effect of Mesenchymal Stem Cells on Experimental Endotoxemia - Zhao, Yiming; Yu, Dingding; Wang, Hongda; Jin, Wang; Li, Xiang; Hu, Yonghao; Qin, Yafei; Kong, Dejun; Li, Guangming; Ellen, Acheampong; Wang, Hao (Frontiers in Cell and Developmental Biology, 2022)
Endotoxemia remains a major cause of mortality in the intensive care unit, but the therapeutic strategy is still lacking. Mesenchymal stem cell (MSC) was reported with a tissue-oriented differentiation ability and an excellent immunoregulatory capacity. However, the immunity signaling pathways that govern MSC modulation effect are not completely understood. In our current study, MSCs (2.5 × 105 /ml) were obtained and stimulated with IFN-γ (20 ng/ml) for 72 h. Gal-9 expression on MSCs was measured by ELISA, RT-PCR, flow cytometry, and immunofluorescence, respectively. Experimental endotoxemia was induced by LPS injection (10 mg/kg, i. p.) followed by the treatment with Gal-9 high-expressing MSCs, unmodified MSCs, and Gal-9 blocking MSCs. Therapeutic effects of MSCs were assessed by monitoring murine sepsis score, survival rate, splenocyte proportion rate, inflammatory mediator levels, and pathological manifestations. The results showed that Gal-9 expressed in MSCs, and this expression was increased in a dose-dependent manner after pre-stimulating with IFN-γ. Adoptive transfer of Gal-9 high-expressing MSCs into modeling mice significantly alleviated endotoxemia symptoms and multi-organ pathological damages. Splenocyte analysis indicated that Gal-9 high-expressing MSCs could promote macrophage polarization to M2-subtype and boost Treg generation. Moreover, there were also attenuated pro-inflammatory mediator expressions (TNF-α, IL-1β, IFN-γ, and iNOS), and increased anti-inflammatory mediator expressions (T-SOD and IL-35) in the sera and damaged organ homogenates. Additionally, we found a higher expression of Gal-9 in liver, lung, and kidney homogenate. Taken together, this study reveals that the optimized immunoregulatory effect of MSCs is strongly correlated with Gal-9 high expression, which provides a novel idea for the investigation of MSC immunomodulatory mechanisms and offers a potential strategy for the treatment of endotoxemia in clinical settings.